Exercise training attenuates angiotensin II-induced cardiac fibrosis by reducing POU2F1 expression - Na Feng; Haiyi Yu; Yueshen Wang; Youyi Zhang; Han Xiao; Wei Gao (Elsevier, 2023)
Background: Exercise training protects against heart failure. However, the mechanism underlying the protective effect of exercise training on angiotensin II (Ang II)-induced cardiac fibrosis remains unclear. Methods: An exercise model involving C57BL/6N mice and 6 weeks of treadmill training was used. Ang II (1.44 mg/kg/day) was administered to induce cardiac fibrosis. RNA sequencing and bioinformatic analysis were used to identify the key factors mediating the effects of exercise training on cardiac fibrosis. Primary adult mouse cardiac fibroblasts (CFs) were used in vitro. Adeno-associated virus serotype 9 was used to overexpress POU domain, class 2, transcription factor 1 (POU2F1) in vivo. Results: Exercise training attenuated Ang II-induced cardiac fibrosis and reversed 39 gene expression changes. The transcription factor regulating the largest number of these genes was POU2F1. Compared to controls, POU2F1 was shown to be significantly upregulated by Ang II, which is itself reduced by exercise training. In vivo, POU2F1 overexpression nullified the benefits of exercise training on cardiac fibrosis. In CFs, POU2F1 promoted cardiac fibrosis. CCAAT enhancer-binding protein β (C/EBPβ) was predicted to be the transcription factor of POU2F1 and verified using a dual-luciferase reporter assay. In vivo, exercise training activated AMP-activated protein kinase (AMPK) and alleviated the increase in C/EBPβ induced by Ang II. In CFs, AMPK agonist inhibited the increase in C/EBPβ and POU2F1 induced by Ang II, whereas AMPK inhibitor reversed this effect. Conclusion: Exercise training attenuates Ang II-induced cardiac fibrosis by reducing POU2F1. Exercise training inhibits POU2F1 by activating AMPK, which is followed by the downregulation of C/EBPβ, the transcription factor of POU2F1.